How the "Meaningful Approach" of Curriculum 1994 can Help Achieve Your Goals - a Newcomers Perspective - Wendy Young Palembang (TEFLIN Journal: A publication on the teaching and learning of English, 1997)
Abstract :This paper looks at the goals of an English teacher and some ways in which we can achieve those goals using "Pendekatan Kebermaknaan" or the "Meaningful Approach" of Curriculum 1994. The linkage between "Pendekatan Kebermaknaan" and the "Com-municative Method" is also noted. The paper refers particularly to the concept of "integration" of the elements of language - such as structure, grammar and vocabulary - with the macro-skills - listening, speaking, reading and writing - as advocated by Curriculum 1994.